Transient analysis of wave propagation in non-homogeneous elastic unbounded domains by using the scaled boundary finite-element method. - Bazyar, Mohammad Hossein (Earthquake engineering & structural dynamics.)
The scaled boundary finite-element method has been developed for the dynamic analysis of unbounded domains. In this method only the boundary is discretized resulting in a reduction of the spatial dimension by one. Like the finite-element method no fundamental solution is required. This paper extends the scaled boundary finite-element method to simulate the transient response of non-homogeneous unbounded domains with the elasticity modulus and mass density varying as power functions of spatial coordinates. To reduce the number of degrees of freedom and the computational cost, the technique of reduced set of base functions is applied. The scaled boundary finite-element equation for an unbounded domain is reformulated in generalized coordinates. The resulting acceleration unit-impulse response matrix is obtained and assembled with the equation of motion of standard finite elements. Numerical examples of non-homogeneous isotropic and transversely isotropic unbounded domains demonstrate the accuracy of the scaled boundary finite-element method.